2023
DOI: 10.2147/jmdh.s391905
|View full text |Cite
|
Sign up to set email alerts
|

Triglyceride Glucose Index Increases Significantly Risk of Hypertension Development in Chinese Individuals Aged ≥45 Years Old: Analysis from the China Health and Retirement Longitudinal Study

Abstract: Objective Our purpose was to explore the relationship between triglyceride glucose (TyG) index and the risk of new-onset hypertension in Chinese individuals aged ≥45 years. Methods From 2011 to 2018, data from the China Health and Retirement Longitudinal Survey (CHARLS) were analyzed. The relationship between TyG index and hypertension was assessed utilizing Cox regression and restricted cubic spline (RCS) plot, and the importance of the TyG index in hypertension develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 32 publications
0
8
1
Order By: Relevance
“…Zheng et al [19] also conducted another single-center, longitudinal study with 4,686 subjects followed up for 9 years, and demonstrated that TyG index could predict incident hypertension among the Chinese population. Of note, another study [28] reached a similar conclusion using a national cohort, but it was limited to middle-aged and older adults over 45 years. In addition, in a recent meta-analysis of 8 studies involving 200,044 general adult participants [43], the relative risk of hypertension was higher for the highest category of TyG index compared with the lowest.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Zheng et al [19] also conducted another single-center, longitudinal study with 4,686 subjects followed up for 9 years, and demonstrated that TyG index could predict incident hypertension among the Chinese population. Of note, another study [28] reached a similar conclusion using a national cohort, but it was limited to middle-aged and older adults over 45 years. In addition, in a recent meta-analysis of 8 studies involving 200,044 general adult participants [43], the relative risk of hypertension was higher for the highest category of TyG index compared with the lowest.…”
Section: Discussionmentioning
confidence: 69%
“…Previous research, however, has primarily focused on the association between TyG index and the incidence of prediabetes [12], diabetes [13], cardiovascular events [14,15], and all-cause mortality [16,17]. Very limited studies were conducted to explore the association of TyG index with new-onset hypertension [18][19][20][21][22][23][24][25][26][27][28]. More importantly, these studies found inconsistence in their findings, including positive [18][19][20][21][22][23][24]27] and non-significant [25,26] associations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Nevertheless, there is a scarcity of cohort studies that particularly investigate the relationship between the TyG index and high blood pressure. [8][9][10][11][12] Additionally, obesity has been linked to IR and hypertension. 13,14 Obesity indicators, such as body mass index, waist circumference, waist-to-hip ratio, and waist-to-height ratio, have been widely used due to their convenient utilization.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence indicates a correlation between the TyG index and cardiovascular disease 7 . Nevertheless, there is a scarcity of cohort studies that particularly investigate the relationship between the TyG index and high blood pressure 8–12 …”
Section: Introductionmentioning
confidence: 99%